Work Environment Relations in Improving the Quality of Employee Work at PT. Pos Indonesia Sidoarjo Branch - Fikri Ari Setiawan; Tri Wahjoedi (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to determine the relationship of the work environment in improving the quality of work of employees at PT. Pos Indonesia Sidoarjo branch. In this study, the method used by the researcher is a qualitative approach through interviews and observations for data collection. From the results of data collection, several conclusions will be drawn from existing interviews so that they can complement the interests of this research. From the results of research and observations, it can be concluded that the relationship between the work environment has a relationship between improving the quality of work of employees, because the work environment is one of the things that influence to build the quality of work of employees in a company. Because the quality of employee work will look good if the company has a good work environment as well.